OTU-007 Treating ileocolonic crohn's strictures with removable-sems – efficacy and safety, a large single centre experience. (8th June 2018) - Das, Ronit; Singh, Rajeev; Din, Said; Chilkunda, Deepika; Krishnamoorthy, Rajesh; Fraser, Catherine; Williams, Jessica; Goddard, Andrew; Norton, Bernard; Hearing, Stephen; Cole, Andrew
Abstract : Introduction: Crohn's patients have a greater than 70% lifetime risk of developing ileocolonic anastomotic strictures. (Rieder et al 2013) The usual management of these strictures has been with surgery or endoscopic balloon dilatation (EBD). Both risk complications, with a reported perforation rate of 4% to 11% with EBD. (Morar et al. 2015) Stenting is a new alternative. We present the largest UK series of Crohn's patients undergoing removable self-expanding-metal-stent' (SEMS) and report on the efficacy and safety of this technique. Methods: Crohn's patients were identified following MR Enterography. Ileocolonic fibrostenotic strictures were assessed for stenting within an IBD MDT setting. Strictures were examined at colonoscopy and stenting not attempted if the stricture was inaccessible, or stenting inappropriate based on endoscopist judgement. Strictures≤6 cm lengths were stented, with the Hannaro Diagmed 'HRC-20–080–230, 80 mm length' stent under combined endoscopic and fluoroscopic guidance. Stents were removed between 6 and 10 days post insertion. Demographic and disease data was collected. All patients were followed up post-procedure median 70 (Range – 18 to 122) weeks. Stenting success was defined as successful placement when endoscopically attempted. Therapeutic success was defined by whether the stented stricture could be crossed colonoscopically at stent retrieval. Results: Eighteen patients were considered for stenting. Four were not suitable – 2 had inflammatory strictures, 1 had an inaccessible stricture (treated with balloon dilatation) and 1 had no apparent luminal stenosis. Fifteen SEMS were placed for 14 patients. Stented patients had median 1 (range 0 to 6) prior surgery. Eleven patients had had prior right hemicolectomy, while 3 had ileal resection only. Attempted SEMS placement was successful in 100% of cases but could not be attempted in one case. Three adverse events were noted. There were 2 patients admitted for abdominal pain, with pain resolving upon stent removal. There was a single asymptomatic stent migration. There were no bleeding events, perforations or any need for emergency surgery. On extended follow up (n=11) 9 of 11 patients reported symptom resolution or improvement. To date none of the patients (n=14) has required surgical intervention during follow up, with a single patient electing for re-stenting. (Ref. Figure 1) Conclusions: In this series, removable SEMS therapy for Crohn's ileocolonic strictures was effective both endoscopically and in relieving symptoms. The absence of perforations appears favourable when compared to rates reported with endoscopic balloon dilatation though a larger controlled study would be needed to test this finding. Observed long term benefit, a low re-intervention rate and no need for surgery during follow up in this series is notable. Safety and comparative efficacy against EBD should be further established with Randomised Control Trial evidence.